Human Resource Organization Theory and its Implications for Human Resource Management Practices - Fitriani, Fitriani; Widiyanto, Eko; Nafrial, Nafrial; Subandi, Subandi; Makbuloh, Deden; Syarifudin, Encep (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study aims to analyze the development of human resource management theory and its implications for effective human resource management practices in modern organizations. In the era of globalization and rapid technological advancement, human resource management is no longer merely concerned with administrative aspects, but also involves more holistic strategies to achieve organizational goals. The method used in this research is a literature review, in which various literatures, including books, scientific articles, and conference papers, are analyzed using NVivo software to identify relevant trends and theories in human resource management. With NVivo, qualitative data analysis can be conducted systematically, allowing researchers to categorize and interpret information in greater depth. The results show that human resource management has undergone a significant transformation from a classic approach that emphasizes operational efficiency to a strategic approach that integrates human resources with the organization's vision and mission. The findings provide valuable insights for practitioners and academics on the importance of responsive and innovative human resource management. Thus, this research is expected to contribute to the development of knowledge in the field of human resource management and provide recommendations for best practices in human resource management.